Ophthalmopathy in the course of Graves-Basedow disease – diagnosis and treatment with regard to the role of the radiotherapy - Ziółkowska, Ewa; Kubiak, Maria; Wiśniewski, Tomasz; Zarzycka, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2007)
Thyroid ophthalmopathy is a most frequent extrathyroid symptom of the Graves-Basedow disease. The etiology is unknown, but supposes that she has an autoimmunologic basis. For the pathogenesis of ophthalmic symptoms accepts three processes: the infiltration, the swelling and the fibrination of the extraocular tissue. Clinically we favour two forms: gentle which appears more often and infiltration-edematous which worse prognoses. The disease can make for the permanent damage of the vision organ. For with the unknown etiology we can use only the symptomatic treatment such as: steroids, radiotherapy and surgical decompression. Purpose of this study is the performance of the present state of the knowledge on the subject of ophthalmopathy in the course of the Graves-Basedow disease with particular reference to the role of the radiotherapy – methods of the treatments seldom used in nonneoplastic diseases.